Climate change in polar marine ecosystems - McMinn, A., (2011)
Climate change will have a significant effect on polar marine ecosystems. While primary production is likely to fall in tropical and temperate seas, it is likely to rise in polar seas. This, however, will only support shorter food chains, which will lead to a decline in major vertebrate species. In polar seas climate change will lead to increased sea-water temperatures, decreased ice cover and a lower pH. Because ice cover is largely impervious to satellite observation, our understanding of polar sea ice and under ice phytoplankton biomass and productivity is still poor. It is generally thought that sea algal communities contribute up to 25% of total annual production in ice covered seas of both Polar Regions but that annual production in the Arctic Ocean is approximately 270 Tg y-1 while in the Antarctic Ocean it is between 980 and 3620 Tg y-1. A simple model of ice reduction, due to global warming, in the Antarctic (the Arrigo and Thomas model) suggests a net increase of 21% in primary production will result in a 50% ice reduction and a further 7% with a 95% ice reduction. However, the location, concentration and position of this production are likely to be quite different to what it is now. A similar, simple model applied to the Arctic suggests that this region will also experience a significant net increase in marine primary production as more of the ocean becomes ice free in summer. A 50% reduction in summer sea ice in the Arctic Ocean would lead to at least an 80% increase in production. Once again, however, the nature, position and concentration of this production is likely to be very different from the current configuration. These changes are likely to induce major trophic realignments in both hemispheres